Development of foam-based layered targets for laser-driven ion beam production. (17th February 2016) - Prencipe, I; Sgattoni, A; Dellasega, D; Fedeli, L; Cialfi, L; Choi, Il Woo; Kim, I Jong; Janulewicz, K A; Kakolee, K F; Lee, Hwang Woon; Sung, Jae Hee; Lee, Seong Ku; et al.
Abstract: We report on the development of foam-based double-layer targets (DLTs) for laser-driven ion acceleration. Foam layers with a density of a few mg cm −3 and controlled thickness in the 8–36 μ m range were grown on μ m-thick Al foils by pulsed laser deposition (PLD). The DLTs were experimentally investigated by varying the pulse intensity, laser polarisation and target properties. Comparing DLTs with simple Al foils, we observed a systematic enhancement of the maximum and average energies and number of accelerated ions. Maximum energies up to 30 MeV for protons and 130 MeV for C 6+ ions were detected. Dedicated three-dimensional particle-in-cell (3D-PIC) simulations were performed considering both uniform and cluster-assembled foams to interpret the effect of the foam nanostructure on the acceleration process.